Death sentence - Smith, Alexander Gordon, 1979- (New York : Farrar Straus Giroux, 2011)
After his failed attempt to escape from Furnace Penitentiary, Alex struggles to survive the bloodstained laboratories beneath where monsters are manufactured, with a death sentence--or worse--hanging over his head.
960
Accelerated Reader AR
Keywords: Prisons -- Juvenile fiction; False imprisonment -- Juvenile fiction; Escapes -- Juvenile fiction; Science fiction